Peer review of the pesticide risk assessment of the active substance dimethomorph - European Food Safety Authority (EFSA); Fernando Alvarez; Maria Arena; Domenica Auteri; Marco Binaglia; Anna Federica Castoldi; Arianna Chiusolo; Angelo Colagiorgi; Mathilde Colas; Federica Crivellente; Chloe De Lentdecker; Isabella De Magistris; et al. (EFSA Journal)
Abstract The conclusions of EFSA following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State The Netherlands and co‐rapporteur Member State Germany for the pesticide active substance dimethomorph and the assessment of applications for maximum residue levels (MRLs) are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012, as amended by Commission Implementing Regulation (EU) No 2018/1659. The conclusions were reached on the basis of the evaluation of the representative uses of dimethomorph as a fungicide applied via foliar spraying on field strawberry and grapevine crops and permanent greenhouse lettuce crops; via drenching on field and permanent greenhouse strawberry crops and via dripping on permanent greenhouse strawberry crops. The peer review also provided considerations on whether exposure to humans and the environment from the representative uses of dimethomorph can be considered negligible, taking into account the European Commission's draft guidance on this topic. MRLs were assessed in potatoes, other root and tuber vegetables (except radishes), stem vegetables (except celery, leeks, globe artichokes, sugar beet, cereal forage and straw). The reliable end points, appropriate for use in regulatory risk assessment and the proposed MRLs, are presented. Missing information identified as being required by the regulatory framework is listed. The concerns are reported where identified.